PENDETEKSIAN DINI TINGKAT KEMANAN INFORMASI BERBASIS ISO 27001 : 2013 MENGGUNAKAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Arini Arini (Cyber Security dan Forensik Digital, 2019)
Information is one of the important assets for the survival of an organization / business, defense security and the integrity of the country, public trust between consumers, so that the availability, accuracy and integrity must be maintained, or commonly abbreviated as CIA (Confidentiality, Integrity & Availability). ISO 27001 is an information security standard published in October 2005 by the International Organization for Standardization (ISO) and International Electrotechnical Commission (IEC). However, until now there has been no tool for companies in Indonesia to do a pre-assessment of the level of information security. Plus the lack of socialization of the rules and the lack of ISO 270001 expert in Indonesia, these are reason why the authors conducted this research. The author begins research by collecting data, by studying literature and interviewing experts to identify problems. After that, in its implementation, this research will be directed (knowledge acquisition) and reviewed directly by an ISO 27001 expert from The British Standard Institution of the United Kingdom (BSI) so that the results are more accurate. After that, the writer determines the weighting method (decision making), scoring method, system development method, and simulation method (testing). The results of the study are in the form of pre-assessment to evaluate the information security assessment index, which will be displayed according to indicators pioneered from ISO 27001: 2013 using AHP (Analytical Hierarchy Process) decision-making methods, as well as web-based making it easier to review.